2016
DOI: 10.1016/j.amjmed.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Re-Initiation of Dabigatran and Direct Factor Xa Antagonists After a Major Bleed

Abstract: Direct oral anticoagulants (DOACs) are a relatively recent addition to the oral anticoagulant armamentarium, and provide an alternative to the use of vitamin K antagonists such as warfarin. Regardless of the type of agent used, bleeding is the major complication of anticoagulant therapy. The decision to restart oral anticoagulation following a major hemorrhage in a previously anticoagulated patient is supported largely by retrospective studies rather than randomized clinical trials (mostly with vitamin K antag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…17 Specific to patients taking DOACs, a large review concluded that following GIB, anticoagulation could resume at 1-week post-bleed. 18 Our findings were consistent with these studies as the majority of both warfarin- and DOAC-treated patients restarted their anticoagulation following a GIB, although we were not able to report the timing upon restarting.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…17 Specific to patients taking DOACs, a large review concluded that following GIB, anticoagulation could resume at 1-week post-bleed. 18 Our findings were consistent with these studies as the majority of both warfarin- and DOAC-treated patients restarted their anticoagulation following a GIB, although we were not able to report the timing upon restarting.…”
Section: Discussionsupporting
confidence: 88%
“…20 For warfarin-treated patients who experience a minor bleeding event, they propose delaying the next dose of warfarin until the INR is less than 2.0 and delaying the next DOAC dose for 1 day. 18 There are limitations in this study that must be acknowledged. First, our sample size and number of different major and CRNM bleeding events was relatively small and therefore both types of bleeding events had to be grouped together as any bleeding events.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Restarting anticoagulation after major hemorrhage has become an area of interest in hopes of mitigating the later TEE disease burden after anticoagulant reversal or cessation for bleeding [24]. Most major hemorrhage patients, especially with GIBs but also many with ICHs, can be restarted in the weeks after the bleeding has stabilized, though guidelines differ on the timing [25,26].…”
Section: Discussionmentioning
confidence: 99%